Optimization of CNC Machining Parameters (Cutting Speed and Feed Speed) on 7075 Aluminum Material to Achieve Minimum Surface Roughness - Harsono, Prijo; Suyono, Suyono; Noviarianto, Noviarianto; Putranto, Wahyu Ari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the optimization of CNC milling machining parameters on 7075 aluminum material to achieve minimum surface roughness through a qualitative research approach. 7075 aluminum is a high-grade aluminum alloy with superior mechanical properties that is widely used in the aviation and automotive industries. The study was conducted by analyzing the effect of cutting speed (Vc) and feed rate (f) on the surface quality of the machined results. The research method uses a qualitative descriptive approach through in-depth observation data collection techniques, structured interviews with operators and technicians, and documentation of the machining process. Research data were obtained from surface roughness measurements using a surface roughness tester (Ra) and visual analysis using machine vision techniques. The results of the analysis show that the combination of an optimal cutting speed of 300-400 m/min and a feed rate of 0.1-0.15 mm/rev produces the lowest surface roughness on 7075 aluminum material. The use of appropriate coolant and maintenance of carbide cutting tools are very significant in achieving optimal surface results. The findings of this study are expected to provide practical guidance for the manufacturing industry in optimizing the CNC machining process for 7075 aluminum material to improve product quality and productive efficiency while still considering industrial sustainability.